1983
DOI: 10.1099/00221287-129-8-2343
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Analysis of Antigenic Determinants of Chlamydia trachomatis by Monoclonal Antibodies

Abstract: Monoclonal antibodies to outer membrane of Chlamydia trachomatis lymphogranuloma venereum (LGV) strain L1 (440-L) were used for antigen characterization. Two separate typespecific antigenic determinants (epitopes) and one species-specific epitope were represented in the major outer-membrane protein (MOMP, molecular weight 40000) of homologous (440-L) and heterologous (IOL-1962, 810-B) L1 strains. One of the type-specific antibodies, the reactivity of which was not affected by oxidation or reduction of the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Salari and Ward were able to extract MOMP from 14 of the 15 then-known serovars (see below) of the chlamydial species Chlamydia trachomatis and noted minor serovar-specific variations in its molecular weight (183). The existence of species-and subspecies-specific epitopes within the protein was noted (37,206), before it became clear that MOMP also contained serovar-specific epitopes (138,162). Even more important, polyclonal (36) and then monoclonal (168,251) antibodies to MOMP were shown to neutralize infectivity of the live organism.…”
Section: Structurementioning
confidence: 99%
“…Salari and Ward were able to extract MOMP from 14 of the 15 then-known serovars (see below) of the chlamydial species Chlamydia trachomatis and noted minor serovar-specific variations in its molecular weight (183). The existence of species-and subspecies-specific epitopes within the protein was noted (37,206), before it became clear that MOMP also contained serovar-specific epitopes (138,162). Even more important, polyclonal (36) and then monoclonal (168,251) antibodies to MOMP were shown to neutralize infectivity of the live organism.…”
Section: Structurementioning
confidence: 99%
“…Examples of observed specificities include genus-; species-; broad subspecies-, as in the B-and C-complex groups; narrow subspecies-, as in the close relationship of serovars E and D (22); and serovar-specific reactions. The molecular basis for such antigenic interrelationships has remained unknown, but recent studies have implicated chlamydial lipopolysaccharide (3) and surface-exposed outer membrane proteins (5,11,20).…”
mentioning
confidence: 99%
“…Stephens et al (19) reported the presence of species-and subspecies-specific determinants in MOMPs, and Matikainen and Terho first showed that MOMPs contain serovar-specific determinants. (20) In addition, several researchers confirmed that anti-MOMP MAbs of C. trachomatis play an important role in identifying the presence of genus-, species-, serovar-, and diverse subspecies-specific determinants in MOMPs. (21) In this study, we compared the DFA test for detecting C. trachomatis infections with a newly developed IFA test.…”
Section: Discussionmentioning
confidence: 96%